An empirical analysis on the determinant of food price inflation in Malaysia - Caroline Geetha; Rosle Mohidin; Vivin Vincent Chandran; Mohd Rahimie Abd. Karim; Retchard Jundam (International Journal of Arts and Sciences, 2015)
The identification on the main determinants of food price inflation in Malaysia was the focus of this study. Using the data from 1960 to 2013, the long run relationship among food price inflation and its determinants (per capita GDP, petrol prices, GST, population and unemployment) were found by utilizing Johansen’s co-integration technique. All determinants affected food price inflation positively and significantly in the long run except GST which was proxied by the sale and service tax was insignificant with correct positive sign. The short run dynamics using the Vector Error Correction Model (VECM) indicated that food price inflation was only affected by per capita GDP, sale tax, petrol price, and population.